(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and electrocardiographic features and identify the genetic variant in a familial case series of Andersen-Tawil syndrome. Subjects and methods: This descriptive retrospective-prospective study included the proband, an elder sister, and two first-degree relatives: her father and younger brother. Data were collected from medical history, previous investigations, and periodic follow-up of the proband. Genetic testing was performed using next-generation sequencing, with confirmation by Sanger sequencing. Results: The elder sister presented with the typical clinical triad of Andersen-Tawil syndrome, including dysmorphic features, periodic paralysis, and bidirectional ventricular tachycardia. The younger brother had severe ventricular arrhythmias, which increased after unsuccessful radiofrequency catheter ablation. The father carried the variant but had no clinical manifestations. All three family members carried the heterozygous missense variant p.Asp71Gly (c.212A > G) in the KCNJ2 gene. Conclusion: This is the first report from Vietnam identifying the p.Asp71Gly variant causing Andersen-Tawil syndrome type 1. The findings demonstrate marked intrafamilial phenotypic variability and highlight the role of genetic testing and Holter electrocardiographic monitoring in early screening for the risk of sudden cardiac death.